1989
DOI: 10.1128/aem.55.3.590-598.1989
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alternate Electron Acceptors on the Metabolic Fate of Hydroxybenzoate Isomers in Anoxic Aquifer Slurries

Abstract: The biodegradation of hydroxybenzoate isomers was investigated with samples obtained from two sites within a shallow anoxic aquifer. The metabolic fates of the substrates were compared in denitrifying, sulfate-reducing, and methanogenic incubations. Under the latter two conditions, phenol was detected as a major intermediate of p-hydroxybenzoate, but no metabolites were initially found with m-or o-hydroxybenzoate. However, benzoate accumulation was noted when metabolic inhibitors were used with these samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Therefore, benzoic acid is not considered an important metabolite of HBA under the experimental conditions of the present study. The biotransformation of HBA to phenol has been reported in an enriched fermentative/methanogenic culture (Tschech and Schink, 1986), anoxic aquifer samples (Kuhn et al, 1989), and a pure culture of Clostridium strain JW/Z-1 (Zhang and Wiegel, 1990). (Fig.…”
Section: Mec Bioanode 273mentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, benzoic acid is not considered an important metabolite of HBA under the experimental conditions of the present study. The biotransformation of HBA to phenol has been reported in an enriched fermentative/methanogenic culture (Tschech and Schink, 1986), anoxic aquifer samples (Kuhn et al, 1989), and a pure culture of Clostridium strain JW/Z-1 (Zhang and Wiegel, 1990). (Fig.…”
Section: Mec Bioanode 273mentioning
confidence: 98%
“…In a review by Schink et al (2000), catechol was regarded as the most slowly degraded divalent phenol under anoxic conditions. Tschech and Schink (1986) reported that phenol, produced from HBA, was slowly degraded in several weeks, whereas Kuhn et al (1989) observed a fast degradation of phenol in 4 days. An earlier study reported that all SA, VA, HBA, catechol and phenol were degraded within 34 days, with more than 60% of the carbon converted to CH 4 and CO 2 (Healy and Young, 1979).…”
Section: Biotransformation Pathways 441mentioning
confidence: 99%
“…Degradation of aromatic compounds in the absence of molecular oxygen has also been documented and is hypothesized to involve reduction of the aromatic ring(s) as a general mechanism (Berry et al, 1987;Fuchs et al, 1994). Decarboxylation and carboxylation of aromatic compounds have been proposed to play important initial roles in the anaerobic degradation of aromatic compounds, especially hydroxybenzoates and phenols (Gallert and Winter, 1992;Hsu et al, 1990;Kuhn et al, 1989;Zhang and Wiegel, 1990a). Zhang and Wiegel (1990b) presented a sequential pathway for the degradation of 2,4-dichlorophenol in both methanogenic sediments and enrichment cultures in which the dechlorinated product, phenol, is converted to benzoate before ring cleavage.…”
mentioning
confidence: 99%
“…Decarboxylation and carboxylation of aromatic compounds have been proposed to play important initial roles in the anaerobic degradation of (hydroxy)arylic acids (e.g., hydroxybenzoic acids) and phenolic compounds in methanogenic environments (2,12,19,24,(33)(34)(35). Zhang and Wiegel (33) proposed a pathway comprised of the sequential actions of at least six bacteria for the mineralization of 2,4-dichlorophenol.…”
mentioning
confidence: 99%